Pengaruh Harga dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Panderman Coffeee Shop di Masa Pandemi Covid-19 - Stella Alvianna; Ika Husnita; Syarif Hidayatullah; Alwin Lasarudin; Estikowati Estikowati (Research Center and Case Clearing House PPM School of Management, 2021)
This study aims to analyze the effect of price and service quality of waiters on customer satisfaction. The research method used in this research is the quantitative method. The data collection instrument used was a questionnaire. The dependent variable in this study is the Customer Satisfaction variable and the independent variable is the Price and Service Quality at Panderman Coffeee Shop Hotel Aria Gajayana Malang. The result is that there is a partially positive and significant effect of price on customer satisfaction who is visiting the Panderman Coffee Shop Hotel Aria Gajayana Malang following the circumstances and the economy of the community during the Covid-19 pandemic. Partially Service Quality has a positive and significant effect on Customer Satisfaction who visits the Panderman Coffee Shop Hotel Aria Gajayana Malang during the Covid-19 pandemic. The quality of service provided by the Panderman Coffeee Shop gives its own impression for customers to come back to the Panderman Coffeee Shop. Based on the simultaneous test (F test) which was conducted to test whether the influence of independent (independent) variables simultaneously on the dependent variable (dependent) so that in this study Price and Service Quality simultaneously had a positive effect on Customer Satisfaction during the Covid-19 pandemic.. Based on the results of the regression test which states that the value of the Price variable regression coefficient is greater than the value of the Service Quality regression coefficient, it can be concluded that during the Covid-19 pandemic, Price has a dominant effect on Customer Satisfaction at Panderman Coffee Shop Hotel Aria Gajayana Malang.